The Effect Of Soaking Feet In Warm Water On Edema Of Pregnant Women's Feet In The Trimester III At ThemidwifeSiswani Lubuk Pakam Clinic In 2025 - Astri Ulina Saragih; Risky Yulanda; Santa Natalia; Sri Andini Herawati (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
Edema is a common complaint experienced by pregnant women, especially in the third trimester, due to physiological changes during pregnancy such as increased blood volume and uterine pressure on the veins. Untreated edema can cause discomfort and health risks. One non-pharmacological method that is believed to be effective in reducing edema is soaking feet in warm water. Objective: This study aims to determine the effect of soaking feet in warm water on the degree of foot edema in pregnant women in the third trimester. MethodThis study used a pre-experimental design with a one group pretest-posttest approach. A sample of 11 pregnant women in the third trimester was selected using purposive sampling. Foot edema data were measured before and after the foot soaking intervention in warm water for several sessions. Data analysis used a Paired Sample t-test to determine the difference in the degree of edema before and after the intervention Result The results showed that the average foot edema score before the intervention was 2.55 with a standard deviation of 0.522, while after the intervention it decreased to 1.73 with a standard deviation of 0.786. Statistical test shows a p-value of 0.000 (p < 0.05), which means there is a significant difference between the edema condition before and after soaking feet in warm water. Conclusion: Soaking feet in warm water has a significant effect on reducing the degree of edema in pregnant women in the third trimester..